Sociodemographic profile and characteristics of whole blood donors in a multispecialist health centre in North Central Nigeria - Jatau, Ezra D.; Udo, Charity I.; Nnawike, Chinedu O.; Zakar, Ayuba; Saleh, Abdulazeez L.; Lagang, Chanjul S.; Ma’an, Victoria T.; Dapus, Obadiah D. (International Journal of Research in Medical Sciences, 2026)
Background: Blood donation is one of humanity’s most noble contributions to medical services, providing invaluable and lifesaving benefits. Mobilising blood donors towards making blood and blood products readily available hinges on understanding the profile and characteristics of blood donors, the reason for this study. Methods: The study was a cross-sectional study carried out between January 2024 and December 2024 involving 3,980 whole Blood donors recruited as walk-in donors in the Jos University Teaching Hospital blood bank or voluntary blood donors during the hospital’s external donor drives. Donor recruitment forms were administered to potential blood donors, while the packed cell volume (PCV) was checked before donor blood collection was carried out. Results: Three thousand, four hundred and fifty-nine (86.91%) males dominated the donor population, with the age group 26-35 accounting for 36.71%. There were more married individuals, 2,210 (55.53%), donating, while self-employed donors were the least. Donors who had previously donated were 2,668 (67.03%), while 1,312 (32.96%) were first-time donors. A history of high blood pressure was reported by 230 (5.78%). Breastfeeding mothers accounted for 0.90% of the donor population. Mean systolic and diastolic blood pressure were 121.73±15.81 and 78.11±9.77 mmHg, respectively, with a mean PCV of 42.98±3.16 percent. Conclusions: The donor population showed some level of awareness by the profile and characteristics recorded. However, further advocacy and public awareness targeted at women, professionals, and the elderly, among other groups, will go a long way in improving donor recruitment, donor retention and availability of safe blood.